Gaining insights into the internal states of the rodent brain through vocal communications. (November 2022) - Karigo, Tomomi
Abstract: Animals display various behaviors during social interactions. Social behaviors have been proposed to be driven by the internal states of the animals that reflect their emotional or motivational states. However, the internal states that drive social behaviors are complex and are often difficult to interpret. Many animals species, such as rodents, use vocalizations for communication in various social contexts. This review provides an overview of the current understanding of mouse vocal communications, its underlying neural circuitry, and the potential to use vocal communications as a readout for the animal's internal states during social interactions. Highlights: Mice display vocalizations during various social interactions. The neural inputs from the forebrain to the periaqueductal gray control vocalizations. Vocal communications can be used as a tool to understand the internal state of the animal.